Efecto de los porcentajes y tipos de extensores cárnicos en las características físicas y rendimiento de nuggets de camarón - Mejía Cano, Denisse Alexandra (2020)
This research work aimed to establish the effect of the percentages and types of meat extenders on the physical characteristics and performance of shrimp nuggets. Different types and percentages of meat extenders were studied which are: isolated soy protein and whey protein, at 3, 4 and 5%, giving a total of six treatments: T1 (3% soy protein), T2 (3% whey protein), T3 (4% soy protein), T4 (4% whey protein), T5 (5% soy protein), T6 (5% whey protein); a completely randomized design (DCA) was used in a 3x2 factorial arrangement with 3 repetitions for each treatment, obtaining 18 experimental units of 2kg each; in which the physical characteristics were evaluated by means of a texture profile analysis (TPA), which allowed determining the firmness, hardness, elasticity, cohesiveness and chewiness of each experimental unit; at the same time the performance of each treatment was determined, and finally an affective test was performed on 50 untrained tasters, in order to determine which of the treatments under study had better characteristics of: color, smell and taste.